2015
DOI: 10.1016/j.tiv.2014.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of untreated and drug-treated differentiated HepaRG cells over a 2-week period

Abstract: Previous works have shown that differentiated human HepaRG cells can exhibit drug metabolism activities close to those of primary human hepatocytes for several weeks at confluence. The present study was designed to evaluate their long-term functional stability and their response to repeated daily drug treatments over a 14-day period, using a transcriptomic approach. Our data show that less than 1% of the expressed genes were markedly deregulated over this two weeks period and mainly included down-regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The cells express most CYPs, phase II enzymes and transporters at levels comparable to cultured primary human hepatocytes and in vivo, making them ideally suited for long-term in vitro clearance and hepatotoxicity studies. Within Predict-IV, Savary et al (2015) evaluated the long-term functional stability of the cell line and their response to drugs after repeated dosing using a transcriptomic approach. The authors found less than 1% of the expressed genes to be markedly altered over the 14-day period.…”
Section: Expression and Activity Of Drug Transporters And Biotransfor...mentioning
confidence: 99%
“…The cells express most CYPs, phase II enzymes and transporters at levels comparable to cultured primary human hepatocytes and in vivo, making them ideally suited for long-term in vitro clearance and hepatotoxicity studies. Within Predict-IV, Savary et al (2015) evaluated the long-term functional stability of the cell line and their response to drugs after repeated dosing using a transcriptomic approach. The authors found less than 1% of the expressed genes to be markedly altered over the 14-day period.…”
Section: Expression and Activity Of Drug Transporters And Biotransfor...mentioning
confidence: 99%
“…In this context, we performed a large-scale analysis to determine the global role of DMSO exposure during the differentiation process. As evaluations of drug toxicity are usually performed with a lower level of DMSO or after DMSO removal [ 53 , 54 , 55 ] we also assessed the effect of DMSO removal after differentiation.…”
Section: Introductionmentioning
confidence: 99%